Casting Grief: A Domestic Performance of Mourning - Bretnall, Luke George (Auckland University of Technology, 2022)
This research explores the presence and absence of grief and questions how casting, as a performance of mourning, might give presence to grief within a domestic space. The research understands domestic space or home as a space of comfort, defined by everyday habitual routines and rhythms. A creative practice of casting has been used as a means to investigate this version of home. The resulting collection of abstracted cast domestic objects is integrated into the home as soft activations. Through a reading of these objects in situ concerning grief and mourning, this research reveals their register of presence and absence within a domestic experience. This process highlights the relationship between spatio-temporal qualities and experiences of grief, positioning the cast objects as markers and activations for these discoveries.